The rising menace of antifungal resistance in dermatophytes among the patients of tinea capitis - Zeeshan, Faiza; waheed, Muhammad Sabir; Uddin, Fakhar (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the epidemiological profile of dermatophytes among patients of tinea capitis and their susceptibility pattern to fluconazole and terbinafine. Method: The cross-sectional study was conducted at the Department of Microbiology, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi, from August to December 2019, and comprised samples of hair and skin from the scalp of tinea capitis patients regardless of age and gender. Demographic details were collected and the samples were processed for direct microscopy and mycological culture. Antifungal susceptibility testing for fluconazole and terbinafine was performed using broth microdilution method. Data was analysed using SPSS 21. Results: Of the 207 patients, 115(55.5%) were males, and 114(55.1%) were children. Alopecia was the most common presenting complaint 141(68.1%), while grey patch tinea was the most characteristic clinical form 53(25.6%). Dermatophytes were yielded in 61(29.5%) cases, non-dermatophytes were isolated in 45(21.7%) specimens, and 101(48.8%) were culture-negative. Among the dermatophytes, trichophyton violaceum was the most common pathogen 21(34.4%), followed by trichophyton mentagrophytes 18(29.5%). Resistance to fluconazole and terbinafine among dermatophytes was recorded in 12(19.7%) and 7(11.5%) isolates, respectively. Conclusion: The frequency of dermatophytes among tinea capitis patients was higher compared to non-dermatophyte species. Antifungal resistance was predominantly seen in trichophyton violaceum and trichophyton mentagrophytes. Key Words: Antifungal agents, Drug resistance, Fluconazole, Terbinafine, Tinea capitis.